Research on penalty mechanism against selfish behaviors in anonymous communication system - SHI Jin-qiao; CHENG Xiao-ming (Tongxin xuebao)
The free-riding problem caused by the selfish behaviors of the anonymous communication system participants was studied in this paper.The effect of the selfish node number on anonymity degree and efficiency of the anonymous systems was statistically analyzed and the analytical results illustrated that neither the anonymity degree nor efficiency could be guaranteed when there existing a lot of selfish nodes.A penalty mechanism based on differential service was proposed to discourage the selfish behaviors of the participants.Theoretical analysis shows that the systems with penalty mechanism can punish the selfish nodes by decreasing of their efficiency,without loss of their anonymity.